The association between the albumin to globulin ratio and thoracic spine bone mineral density in adolescents: NHANES 2011–2016 - Yan, Haoyu; Yang, Jie; Dai, Yancheng; Li, Yan; Zhang, Peng; Li, Liuyan (Frontiers in Nutrition, 2025)
BackgroundNumerous studies have demonstrated a strong correlation between osteoporosis and nutritional status and inflammation, while albumin and globulin are important references for nutritional status and inflammation, respectively. The albumin to globulin ratio (AGR), which combines the levels of albumin (ALB) and globulin (GLB), is a new comprehensive index that offers a more precise reflection of the inflammatory state of the body and its nutritional status. However, the connection between AGR and thoracic spine bone mineral density (BMD) remains poorly understood. The purpose of this research was to examine the link between the AGR and thoracic spine BMD in adolescents.MethodsThis study used the most recent data from the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2016, and used weighted multivariate linear regression modeling to examine the correlation between AGR and thoracic spine BMD in adolescents. Threshold effects and non-linear relationships were assessed using a smoothed curve-fitting algorithm alongside threshold effects analysis. Furthermore, subgroup analyses and interaction tests were performed.ResultsThe study comprised a total of 3,000 participants who were all aged 20 years or younger. Based on weighted multivariate linear regression analysis, in the fully adjusted model, a significantly higher thoracic spine BMD was found in the highest AGR quartile compared to the lowest AGR quartile (p < 0.05). After adjusting for variables, subgroup analyses showed no significant interaction effects. The study of threshold effects and the fitting of smooth curves identified a specific threshold effect for AGR and thoracic BMD with an inflection point of 1.237, after which AGR was significantly positively correlated with thoracic spine BMD.ConclusionThe study identified a notable positive correlation between AGR and adolescent thoracic spine BMD. This finding indicates a potential correlation between higher AGR and higher thoracic spine BMD, which may be indicative of a reduced risk of developing Osteoporosis (OP). This emphasizes the importance of considering nutritional and inflammatory status in the prevention of OP, thereby validating the utilization of AGR as a pivotal marker for the development of early intervention methodologies.